Perspektif Alkitab Tentang Kesetaraan Gender dan Implikasinya Bagi Pendidikan Agama Kristen - Yunardi Kristian Zega (Didache: Journal of Christian Education, 2021)
Gender equality is still an interesting issue to be discussed today. Most people, especially those living in various regions in Indonesia, still misinterpret this. Gender equality is seen as an act that puts women first. In Christian circles, this thought is caused by Christian leaders in the past who gave teachings about gender who had unfair treatment between men and women. To provide a solution to these problems, the author uses qualitative research with the literature study method. The author finds that, gender is a characteristic that can be exchanged between each other and can be shared by both. Allah distinguishes the sexes but does not differentiate between the roles of the two. Thus, PAK plays a vital role in building gender understanding in the family and community, especially in the field of education, and in the field of education.Â Â